2022
DOI: 10.3847/1538-4357/ac847c
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low-mass White Dwarf Stars Observed in Gaia DR2 and LAMOST DR8

Abstract: We present the first results from our ongoing project to study extremely low-mass (ELM) white dwarfs (WDs) (M ≤ 0.3M ☉) with the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) spectra. Based on the LAMOST DR8 spectral database, we analyzed 136 ELM WD candidates selected from Gaia DR2 data and 12 known objects previously identified by the ELM Survey. The atmospheric parameters and radial velocities of these stars were obtained by fitting the LAMOST low-resolution spectra. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Many of the remaining binaries not reported as ELM white dwarf candidates in Pelisoli & Vos (2019) were excluded in their color cuts used to remove cataclysmic variables and white dwarf + M dwarf binary contaminants. Wang et al (2022) used LAMOST DR8 low-resolution spectroscopy to refine the candidate list of Pelisoli & Vos (2019) further and identified 21 high-probability ELM white dwarfs based on spectroscopic fits to the low-resolution LAMOST data, including two of the new binaries we present in this work. Wang et al (2022) identified J0215+0155 with atmospheric parameters of T eff = 10,540 ± 40 K and , and v rad,2 = 94.9 ± 5.4 km s −1 , the first of which is in excellent agreement with the atmospheric parameter estimates from the fits presented in this work.…”
Section: Comparison With Other Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the remaining binaries not reported as ELM white dwarf candidates in Pelisoli & Vos (2019) were excluded in their color cuts used to remove cataclysmic variables and white dwarf + M dwarf binary contaminants. Wang et al (2022) used LAMOST DR8 low-resolution spectroscopy to refine the candidate list of Pelisoli & Vos (2019) further and identified 21 high-probability ELM white dwarfs based on spectroscopic fits to the low-resolution LAMOST data, including two of the new binaries we present in this work. Wang et al (2022) identified J0215+0155 with atmospheric parameters of T eff = 10,540 ± 40 K and , and v rad,2 = 94.9 ± 5.4 km s −1 , the first of which is in excellent agreement with the atmospheric parameter estimates from the fits presented in this work.…”
Section: Comparison With Other Surveysmentioning
confidence: 99%
“…In total, previous ELM Survey studies have constrained the orbits and atmospheric parameters of 120 unique low-mass white dwarf binaries (Brown et al 2020;Kosakowski et al 2020;Brown et al 2022). Similar studies have created catalogs of ELM white dwarf candidates using Gaia DR2 astrometry (see Pelisoli & Vos 2019) and single-epoch spectroscopy from LAMOST DR8 (see Wang et al 2022), many of which still require follow-up observations to confirm their nature.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently more than 150 known ELM WDs (e.g. Brown et al 2022;Kosakowski et al 2023, and references therein), as well as ELM WD candidates (Pelisoli & Vos 2019;Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to searches from individual observations, one can perform a CWDB search with a larger scale. Several surveys can be used to pick potential CWDB candidates, like the Catalina Real-time Transient Survey (CRTS; Breedt et al 2014), the Global Astrometric Interferometer for Astrophysics (Gaia; Geier et al 2017;El-Badry et al 2021a;Gentile Fusillo et al 2021;Rebassa-Mansergas et al 2021;Torres et al 2022), the Optical Gravitational Lensing Experiment (Wevers et al 2016), the Palomar Transient Factory (van Roestel et al 2017(van Roestel et al , 2018Burdge et al 2019b), the All Sky Automated Survey for SuperNovae (Rivera Sandoval et al 2022), the Transit Exoplanet Survey Satellite (Wang et al 2020;Pichardo Marcano et al 2021;Hernandez et al 2022), the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST; Wang et al 2022b), and most recently the Zwicky Transient Facility (ZTF; Burdge et al 2020aBurdge et al , 2020bCoughlin et al 2020;Ofek et al 2020;Szkody et al 2020;Kupfer et al 2021;Szkody et al 2021;Keller et al 2022;McWhirter & Lam 2022). Repeated observations of the same sources can reveal optical variability, and some of these surveys can be used, and have been used, to determine the periodicity.…”
Section: Introductionmentioning
confidence: 99%